2014
DOI: 10.1585/pfr.9.3402087
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Spectral Measurements in the D-Module of the GAMMA 10/PDX End-Cell

Abstract: In this paper, results of spectral measurement in the end-cell of the GAMMA 10/PDX are described. A spectral measurement system consisting of two spectrometers was developed in order to measure the detailed radiation behavior in D-module. Firstly, angular dependence of the V-shaped target plate on the spatial distribution of the Hα radiance was investigated. It is found that the spectral distribution in Hα intensity along the axial direction is affected by the angle of the target plate. Next, in the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Figure 2(b) shows the relationship between FWHM and plenum pressure of SMBI with Laval nozzle. The FWHM value with Laval nozzle is lower than that for the both cases with straight nozzle and without nozzle [5,6]. Besides, in all plenum pressure, the FWHM value is lower than the plasma diameter.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Figure 2(b) shows the relationship between FWHM and plenum pressure of SMBI with Laval nozzle. The FWHM value with Laval nozzle is lower than that for the both cases with straight nozzle and without nozzle [5,6]. Besides, in all plenum pressure, the FWHM value is lower than the plasma diameter.…”
Section: Resultsmentioning
confidence: 68%
“…An SMBI experiment in GAMMA 10 has been performed by three conditions; without any nozzle, straight nozzle and Laval nozzle. The first experimental results of SMBI by both straight nozzle and without any nozzle showed that SMBI achieved higher density plasmas at the core region than the conventional gas puffing [5,6]. In addition, the penetration depth is high in the case of straight nozzle than without nozzle [6].…”
Section: Introductionmentioning
confidence: 99%
“…In magnetically confined plasmas, the proper control of gas fueling is very important issue. The supersonic molecular beam injection (SMBI) is an effective fueling method developed by L. Yao, et al [1] which can inject neutral particle deeper into the core plasma compared to conventional gas puffing [2,3]. SMBI system is very simple and economically feasible to develop.…”
Section: Introductionmentioning
confidence: 99%
“…eling method to produce high density plasmas [2,3]. Investigation of neutral particle behavior during SMBI is an important task for understanding the plasma-neutral interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the heat load to the divertor plate by promoting the radiation cooling is an important subject to form the detached plasma [1][2][3].…”
Section: Introductionmentioning
confidence: 99%